2011
DOI: 10.1007/s00540-010-1090-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of rocuronium-induced neuromuscular block by sugammadex is independent of renal perfusion in anesthetized cats

Abstract: Sugammadex rapidly and effectively reversed rocuronium-induced neuromuscular block in anesthetized cats, even when both renal pedicles were ligated and renal elimination of the drugs was no longer possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Experiments performed in anaesthetized cats, in which both renal arteries were completely occluded, support these findings [42].…”
Section: Discussionsupporting
confidence: 76%
“…Experiments performed in anaesthetized cats, in which both renal arteries were completely occluded, support these findings [42].…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that sugammadex is mainly eliminated by excretion through the kidneys. 7,8 Staals and colleagues 16 reported that reversal of a rocuronium-induced neuromuscular blockade is independent of renal perfusion by ligating renal pedicles in anesthetized and paralyzed cats 002; values represent mean ± SEM, n = 6. GV, glomerular vacuolation; TD, tubular dilatation; VVH, vascular vacuolation and hypertrophy; TCDN, tubular cell degeneration and necrosis; DBS, dilatation in Bowman's space; THC, tubular hyaline casts; LI, lymphocyte infiltration; TCS, tubular cell sloughing.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors, used to reverse the effects of nondepolarizing neuromuscular blockers, have important disadvantages such as residual block and hemodynamic side effects [1,2]. The most important reasons for choosing sugammadex, a gamma cyclodextrin derivative which has entered use in recent years, are its superior properties during extubation and recovery stages and low risk of residual block [3].…”
Section: Introductionmentioning
confidence: 99%